The intelligent company : five steps to success with evidence-based management - Marr, Bernard (Chichester, U.K. : John Wiley & Sons, 2010)
This practical book provides managers with five essential steps to improve their business intelligence and allow them to carry out the kind of reality check they need to maintain competitive advantage for their organization. The author's simple, step-by-step model offers managers a vital tool for analyzing their business and improving performance.
The data knowledge crunch -- The evidence-based management model -- Identifying objectives and information neds -- Collecting the right data -- Analyse the data and gain insights -- Turning information into actionable knowledge--Conclusions and action checklist.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
John Wiley and Sons
Keywords: Business intelligence; Business planning; Management; Gestion; management; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Business intelligence; Business planning; Management